Стійкість та адаптивність малих і середніх підприємств під час пандемії Covid -19: аналіз бібліографії та перспективи - Arsawan, I Wayan Edi; Supartha, I Wayan Gede; Rustiarini, Ni Wayan; Sita Laksmi, Putu Ayu (Dr. Viktor Koval, 2021)
Introduction. The Covid 19 pandemic has challenged SMEs to continue to innovate, develop and maintain sustainability. Various efforts have been made to be able to have performance and competitiveness. Covid-19 provides lessons on how SMEs must be agile and resilient to turbulence, especially the global crisis so that they can carry out risk mapping, take important lessons and build relevant strategies. Aims and Task. This study aims to map the literature on organizational agility and organizational resilience in SMEs by conducting a bibliography analysis on 932 papers published in 2010-2021 in the Scopus bibliography. Result. Based on the results of the network visualization, there are seven main clusters. From the results of the overlay visualization, a supply chain is the most important variable concerning organizational agility and organizational resilience in realizing sustainability. Meanwhile, in the density visualization aspect, variables with a very high probability as future research topics such as supply management, supply chain sustainability, sustainable development goals, human resource management, chain resilience, sustainable supply chain management, agile, urban resilience, visibility, supply chain design, resilient supplier selection, and enterprise architecture. Conclusion. The present study produces a visual trend of organizational agility and resilience in SMEs sector that can be used as a references, guidance and proposed for further researchers in exploring research topics, bridging the gap in the literature, building expertise in related topic, increasing the number of citations, and enhance international networking among authors all around the world. Research regarding organizational agility and resilience could be a strategic and essential because of every organization need to sustain their existance, minimize potential risk both financial and non-financial.